Plato in therapy: a cognitivist reassessment of the Republic's idea of Mimesis - Grethlein, Jonas (Journal of aesthetics and art criticism, 2020)
The Republic’s ban on poetry is a major reason for the prominent place that liberal critics assign to Plato among the enemies of the open society, Friedrich Nietzsche's description of Plato as “the greatest enemy of art Europe has yet produced” being often cited. In this article, I argue that, while Plato's ethical stance remains unacceptable for most readers today, his understanding of aesthetic experience in the Republic appears highly perceptive when seen in the light of cognitive studies and can be thought-provoking for current debates. As I try to show in the first half of the article, Plato's assessment of responses to poetry and theater resonate with embodied and enactive views of cognition. To corroborate this thesis, I point out in the second half that while theory has been blind to the significance of Plato's aesthetics, its major ideas are substantiated in practice. Contemporary psychotherapy and its increasing deployment of virtual reality unknowingly and with the opposite intent realize Plato's approach to the cognitive dynamics and ethical potential of aesthetic experience.